PENGARUH BRAND POSITIONING DAN BRAND EQUITY TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR YAMAHA - Jatmiko, Jatmiko; Setyawati, Retno Lies (Lembaga Penerbitan Unversitas Esa Unggul, 2015)
This study aims to determine whether the brand positioning and brand equity that include brand awareness, perceived quality, brand association, brand loyalty have an influence on purchasing decisions Yamaha motorcycles, as well as what factors are the most dominant among the brand positioning, brand awareness, perceived quality, brand association, brand loyalty, the purchasing decision of Yamaha motorcycles in the Housing Karawaci Tangerang.The population in this study are all consumers of Yamaha motorcycles in the Housing Karawaci Tangerang who buy and use a Yamaha motorcycle. A sample drawn from the population to be used in research as respondents as many as 100 people. Sampling technique using non-probability sampling method by purposive sampling. The analytical method used is the Multiple Linear Regression Analysis.The results showed that the analysis of the factors that influence purchasing decisions Yamaha motorcycle individually is the brand positioning has an influence on purchasing decisions with significant value 0.032> 0.05, and brand equity, especially perceived quality has an influence on purchasing decisions with significant value 0.029 < 0:05. Other elements of brand equity consisting of brand awareness does not have the influence on purchasing decisions with significant value 0496> 0.05, brand association has no influence on purchasing decisions with significant value 0.900> 0.05, and brand loyalty has no influence on purchasing decisions with significant value 0.296> 0.05.Further analysis of the factors that influence purchasing decisions Yamaha motorcycle jointly between the brand positioning and brand equity consisting of brand awareness, perceived quality, brand association, and brand loyalty effect with significant value 0.011 <0.05. From the analysis of the factors that influence the purchase decisions of the five variables analyzed, the most dominant influence purchasing decisions Yamaha motorcycle seen based on the value Unstandarized Coefficients (B) is variable perceived quality with the coefficient of the biggest (0.266) compared with the value coefficients of other variables.Â KeywordsÂ :Â Brand Positioning, Brand Awareness, Perceived Quality, Brand Association, Brand Loyalty and Purchase Decisions.